Infection and transmission of COVID-19 among students and teachers in schools in Japan after the reopening in June 2020 - Koji Wada; Nobuhiko Okabe; Yugo Shobugawa (BMJ Publishing Group, 2020)
We aimed to investigate the confirmed COVID-19 cases among students and teachers in elementary schools (ages 6-12 years) and junior high schools (ages 13-15 years) in Japan between 1 June and 31 July 2020. We requested all schools to provide reports when students or teachers tested positive for COVID-19. A total of 207 cases were reported among students. Household transmission was identified as the dominant transmission route, confirmed in 71.4% of elementary schools and 60.3% of junior high schools. A total of 39 cases were reported among teachers, of which transmission route was unknown in 72.4% of elementary schools and 90.0% of junior high schools.